Comparison of Present State and Possibilities for Development of Basic Training of Voluntary Fire Units Members in Slovak Republic and Czech Republic - Drotárová, Josefína; Kavan, Štěpán (Vysoká škola evropských a regionálních studií, 2018)
The aim of the contribution is to examine the current state and possibilities of basic preparation of voluntary fire brigades members of the Slovak Republic and the Czech Republic and their comparison. The secondary objective is to identify shortcomings and opportunities for improving training of selected fire brigades with the emphasis on basic training. Training of fire-fighting units members – voluntary fire brigades of the municipality is aimed at acquiring knowledge, skills, physical fitness and habits necessary for carrying out fire-fighting activities and performing rescue work for various extraordinary events. The methodological procedure is focused on the study of professional resources and legislative basis in relation to the selected type of fire-fighting units as well as information from interviews conducted with experts. The information obtained from the literature research is analyzed and sorted so that partial knowledge can be combined in the content units by the method of synthesis. The obtained information is compared and evaluated from the point of view of the Slovak Republic and the Czech Republic. Like the Czech Republic, the Legislation of the Slovak Republic determines the obligation to complete compulsory basic training for each member of the voluntary fire brigade of the municipality, who wants to participate in the intervention. For specific functions, the scope of the training is determined specifically for that function. Tactical exercises, perfection, cyclical preparation are also used. The resulting reflection compares national approaches and proposes solutions to improve the existing training.
Komparace současného stavu a možnosti rozvoje sborů dobrovolných hasičů ve Slovenské republice a České republice
Keywords: comparison; development; basic training of fire units members; porovnání; rozvoj; základní příprava jednotek požární ochrany